The suffering body in sport : shifting thresholds of pain, risk and injury - Young, Kevin (Bingley, U.K. : Emerald Publishing Limited, 2019)
Public awareness of and sensitivity to questions of pain, risk and injury in sport is more acute than ever before. Whether it is questions of what sport (and fans) can realistically and responsibly expect of athletes, how revered practices almost inevitably culminate in suffering bodies, or the widespread attention being paid to injury outcomes (especially concussion), it is clear that sport in many settings currently operates in a climate that is both more scientifically and medically aware and more sensitive to risk 'outcomes'.This volume closely explores the full panorama of pain, risk and injury in the cultural, organizational and legal orbits of sport spaces. Aimed at students, researchers as well as applied professionals, the volume sets the cultural, structural and organizational context that gives rise to pain, risk and injury in the first place, provides substantive empirical examples from diverse sports arenas, looks at the key issues and dimensions of pain, risk and injury in the social consciousness today, and explores three different 'spins' on making sense of the subject matter -- from the position of the issue of consent and the courts, from the position of exploitation and corporate victimization, and from the understudied position of why athletes exit sport as an outcome of pain and injury and with what consequences.This timely and needed addition to the sport literature is an exciting 'on-the-bubble' treatment of a topic that is increasingly troubling authorities and affecting how and whether sport is undertaken.
Prelims -- Introduction -- Sport and risk culture -- The rationalization of healthcare in modern sport: from policy to practice -- Risk in lifestyle sports: the case of parkour -- An enduring event: 20 years of one athlete's negotiation with pain at the Ironman Triathlon World Championships -- Injury, pain and risk in the paralympic movement -- Sports-related brain injury: concussion and chronic traumatic encephalopathy -- Going public with pain: athlete stories of disordered eating in discourse -- Suffering in sport -- Complexities in Canadian legal approaches to sports injury -- Regulating the harmful, injurious and risky business of professional wrestling -- When the athletic body fades: sporting exit and identity transitions -- Index.
Includes index.
Print version record
Keywords: Sports injuries -- Social aspects; Sports & Recreation -- General; Sociology: sport & leisure